2013
DOI: 10.2752/175303713x13636846944321
|View full text |Cite
|
Sign up to set email alerts
|

Choosing between the Emotional Dog and the Rational Pal: A Moral Dilemma with a Tail

Abstract: Neuroscientific studies indicate moral cognition involves a cognitive struggle between two systems in the brain: the emotional "hot" system and the rational "cold" system. Past research has shown that when presented with personal dilemmas, individuals showed greater brain activity in the hot system areas. However, when further probed about their decisions, moral dumbfounding often occurs. Family selection may help explain moral judgments. Oftentimes, people consider their pets as part of their family. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
0
22
0
2
Order By: Relevance
“…Taking these responses to be indicators of a state of dumbfoundedness, it appears that moral dumbfounding can be evoked in face-to-face and online contexts. As such, the research presented here may be seen as more support for the existence of intuitionist theories of moral judgement (e.g., Cushman et al, 2010;Greene, 2008;Haidt, 2001;Hauser et al, 2008;Prinz, 2005) over rationalist theories (e.g., Kohlberg, 1971;Topolski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking these responses to be indicators of a state of dumbfoundedness, it appears that moral dumbfounding can be evoked in face-to-face and online contexts. As such, the research presented here may be seen as more support for the existence of intuitionist theories of moral judgement (e.g., Cushman et al, 2010;Greene, 2008;Haidt, 2001;Hauser et al, 2008;Prinz, 2005) over rationalist theories (e.g., Kohlberg, 1971;Topolski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years moral dumbfounding has been challenged by a number of authors (e.g., Gray et al, 2014;Jacobson, 2012;Sneddon, 2007;Wielenberg, 2014), arguing, in line with rationalist theories of moral judgement (Kohlberg, 1971;Narvaez, 2005;Topolski, Weaver, Martin, & McCoy, 2013), that moral judgements are grounded in reasons. Recent work by Royzman, Kim, and Leeman (2015), involving a series of studies focusing on the Incest dilemma, identified two reasons that may be guiding participants' judgements.…”
Section: Challenges To Moral Dumbfoundingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moral decisionmaking scenarios have been the basis of numerous research studies on moral reason ing (e.g., Topolski, Weaver, Martin, & McCoy, 2013). In some classic scenarios, research participants were asked to choose whether to kill one individual in order to save a larger group of people.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that, when participants were presented with a dilemma in which there was a limited supply of a drug, nearly all the participants said that they would give their pet, rather than a stranger, the drug under at least one circumstance (Cohen, 2002). In a related study, researchers examined the likelihood that one would save an animal's life over a human life (Topolski et al, 2013). Specifically, Topolski et al (2013) manipulated the degree of relatedness to the participant (i.e., sibling, grandparent, close friend, distant cousin, hometown stranger, and foreign tourist) and measured the effect of related ness on participants' likelihood of saving a human or their pet.…”
Section: The Effects Of Age and Sex On Saving Pets Over Humansmentioning
confidence: 99%